Answer:
infinite solution
Step-by-step explanation:
because it is a linear equation.
Answer: -10
Step-by-step explanation:
Simplifying
-3(y + 5) = 15
Reorder the terms:
-3(5 + y) = 15
(5 * -3 + y * -3) = 15
(-15 + -3y) = 15
Solving
-15 + -3y = 15
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '15' to each side of the equation.
-15 + 15 + -3y = 15 + 15
Combine like terms: -15 + 15 = 0
0 + -3y = 15 + 15
-3y = 15 + 15
Combine like terms: 15 + 15 = 30
-3y = 30
Divide each side by '-3'.
y = -10
Simplifying
Well I would solve it but where's the problem?
The key features of
polynomials are the vertex, axis of symmetry, x and y intercepts.
<span>1.
</span>The degree will help you find the end behavior.
<span>2. </span>The vertex shows you where it changes concavity.
<span>3. </span>X and y intercepts give you a couple of points
of reference.
<span>4. </span>Axis of symmetry is only applicable to even
degree polynomials.
I am hoping that these answers
have satisfied your queries and it will be able to help you in your endeavors, and
if you would like, feel free to ask another question.